2013
DOI: 10.13080/z-a.2013.100.040
|View full text |Cite
|
Sign up to set email alerts
|

Paprastojo žieminio kviečio (Triticum aestivum L.) veislių derliaus svyravimo erdvinio panašumo Vakarų Lenkijoje analizė

Abstract: The study makes use of yields of winter wheat (Triticum aestivum L.) cultivars obtained in a series of PostRegistration Variety Testing System, experiments conducted in 2006-2008 at 12 locations of diverse edaphic and climatic conditions of Western Poland. The experiments were carried out at two intensity levels in two replications. The paper presents an analysis pertaining to the intensive level of cultivation, which differed from the standard cultivation in nitrogen fertilization higher by 40 kg ha -1 , full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…High cereal yield usually depends on low precipitation during winter and in April, whereas higher precipitation is necessary at the straw-shooting and flowering stages. Bujak [47] implied a lack of correlation between yield and precipitation sum. Erekul and Kohn [48] demonstrated that a continued water deficit and above-average temperatures during grain filling lowered the TKW of winter wheat, which was not confirmed in the present study.…”
Section: Yield and Its Componentsmentioning
confidence: 99%
“…High cereal yield usually depends on low precipitation during winter and in April, whereas higher precipitation is necessary at the straw-shooting and flowering stages. Bujak [47] implied a lack of correlation between yield and precipitation sum. Erekul and Kohn [48] demonstrated that a continued water deficit and above-average temperatures during grain filling lowered the TKW of winter wheat, which was not confirmed in the present study.…”
Section: Yield and Its Componentsmentioning
confidence: 99%
“…The constant development of the PRVT research system and the wide evaluation of regis tered varieties significantly help in making the right choice. Such experiments are a valuable source of information for farmers in terms of the selection of varieties for cultivation (Bujak et al 2012a(Bujak et al , 2012b(Bujak et al , 2013.…”
Section: Plon / Yieldmentioning
confidence: 99%
“…The values of each application rate and the results of yield of winter and spring wheat, winter and spring barley, winter and spring triticale, winter rye and spring oats were taken from the Polish Post-Registration Variety Testing System (PRVTS) (Bujak et al, 2013). The PRVTS was established to evaluate the yield and other related traits of newly released cultivars through multienvironmental trials and give reliable recommendation to Polish farmers.…”
Section: Greenhouse Gas (Ghg) Emission Calculationsmentioning
confidence: 99%